Videnskabelig (u)redelighed - også et tema for lingvistik - Bergenholtz, Carsten (HERMES - Journal of Language and Communication in Business, 2005)
The debate about scientiﬁc dishonesty over the last few years has revealed differences and confusion regarding scientiﬁc dishonesty. Every branch of science ought to have well-established criteria for scientiﬁc dishonesty, to be able to distinguish between sloppy science and dishonest science. Sc. dishonest behaviour is characterized by being dishonest or reckless, and by twisting the scientiﬁc message. The aim of this article is to a) provide a list of criteria to deﬁne scientiﬁc dishonesty, and b) exemplify and discuss speciﬁc linguistic aspects of the discussion. Furthermore it will be argued that agreeing on common rules is not enough as general rules can be interpreted differently. Therefore a common judgement is necessary, i.e. a committee, either local or national. It is recommended that any local institution establishes a committee of their own.